Anisotropic magnetoresistance as evidence of spin-momentum inter-locking in topological Kondo insulator SmB6 nanowires. Issue 48 (8th December 2021) - Cui, Yugui; Chu, Yi; Pan, Zhencun; Xing, Yingjie; Huang, Shaoyun; Xu, Hongqi
Abstract : The anisotropic magnetoresistance reveals a signature of spin-momentum inter-locking in surface-states of SmB6 nanowires. Figure (a) in-plane magnetic field magnetoresistance; (b) temperature dependences of the anisotropic magnetoresistance. Abstract : SmB6, which opens up an insulating bulk gap due to hybridization between itinerant d-electrons and localized f-electrons below a critical temperature, turns out to be a topological Kondo insulator possessing exotic conducting states on its surface. However, measurement of the surface-states in SmB6 draws controversial conclusions, depending on the growth methods and experimental techniques used. Herein, we report anisotropic magnetoresistance (AMR) observed in the Kondo energy gap of a single SmB6 nanowire that is immune to magnetic dopant pollution and features a square cross-section to show high-symmetry crystal facets. The AMR clearly shows a cosine function of included angle θ between magnetic field and measuring current with a period of π. The positive AMR is interpreted by anisotropically lifting the topological protection of spin-momentum inter-locking surface-states by rotating the in-plane magnetic field, which, therefore, provides the transport evidence that supports the topologically nontrivial nature of the SmB6 surface-states.